Explanation of the degree of Divine Knowledge in the degree of Decrees of fate in Molla Sadra and Allama Tabatabai\\\'s views - Alireza Khajegir (Comparative Theology, 2013)
The Sadraee's transcendental philosophy in theology affected by the authentic Divinity texts and discussions and has inspired in resolving many of the theological and philosophical problems of this school. Therefore, this school can be considered as the most prominent school. Although, Molla sadra does not know enough the argument and arguing without conscience and purification of self, but, the most based on imported sources of revelation and interpretations of Imams (AS) and believes that truths of faith are not possible except by purifying heart from the whims, thinking of the Divine verses, hadith of the Prophet (The Prophet's massage) and his tribe, and following the way of the pious men. Proposing the problem of Divine Decrees of fate in transcendental philosophy and explaining its principles that brought up in both the philosophical texts and exegesis of the followers of transcendental philosophy are of the most important Instances that this school takes impression from religious texts.